Efficacy and safety of Subetta add-on therapy in type 1 diabetes mellitus: The results of a multicenter, double-blind, placebo-controlled, randomized clinical trial. (August 2018) - Mkrtumyan, Ashot; Romantsova, Tatyana; Vorobiev, Sergei; Volkova, Anna; Vorokhobina, Natalia; Tarasov, Sergey; Putilovskiy, Mikhail; Andrianova, Elena; Epstein, Oleg
Abstract: Background: To examine efficacy of Subetta as an add-on to insulin therapy in patients with type 1 diabetes mellitus (T1DM) a multicenter, double-blind, placebo-controlled, randomized clinical trial was performed. Derived by technological treatment of antibodies to insulin receptor β-subunit and endothelial NO synthase Subetta was previously proved to activate insulin signaling pathway. Methods: A total of 144 randomized patients with poor glycemic control in basal-bolus insulin regime were included in intention-to-treat analysis in Subetta add-on therapy or placebo (n = 72 in both groups). Hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), basal and prandial insulin doses, number of hypoglycemia episodes confirmed by self-monitoring of blood glucose were recorded for 36 weeks. Results: The baseline characteristics of subjects did not differ between the two groups. HbA1c mean (±standard deviation) change was −0.59 ± 0.99% (95% CI −0.84 to −0.37) after 36 weeks in Subetta (vs. −0.20 ± 1.14%; 95% CI −0.44 to 0.11 in placebo; p = 0.028). The rate of overall hypoglycemia events was 7.9 per patient year (95% CI 7.1–8.6) in Subetta group and 7.6 (95% CI 6.9–8.4) in Placebo group (p = 0.63). The basal and total insulin doses did not change at the end of 36 weeks in both groups. Conclusions: Subetta add-on therapy boosting insulin activity and improving glycemic control in patients with T1DM is proved to be beneficial. Clinical trial registration: ClinicalTrials.gov identifier: NCT01868594.